NOVEL HPTLC-DENSITOMETRIC METHOD FOR THE ESTIMATION OF TERIFLUNOMIDE IN TABLET DOSAGE FORM - Vishwas, T. S.; Gurupadayya, B. M.; Jain, Rupshee (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: The current work is intended towards the development of a novel, simple and precise high-performance thin layer chromatographic (HPTLC) method coupled with a densitometer for the estimation of teriflunomide (TEF) present in the marketed formulation. Methods: The chromatographic development was performed on aluminum plates coated with silica gel 60 F254 using toluene: ethyl acetate: glacial acetic acid (7.5:2: 0.5 v/v/v) as the mobile phase. Densitometric scanning was achieved at the absorbance maxima, UV 284 nm. Results: Well separated band was observed with Rf value 0.46. The calibration curve plotted in the concentration range 100-700ng/band exhibited an excellent linear relationship with the r2 value of 0.9928. The method was found to comply with all the validation parameters as per the ICH guidelines. Conclusion: The method ensures minimal use of mobile phase with minimal run time compared to other reported analytical methods. This validated method can be used by quality control laboratories for the routine quantitative analysis of tablets consisting of Teriflunomide.